1995
DOI: 10.1523/jneurosci.15-01-00342.1995
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine modulation of transient potassium current evokes phase shifts in a central pattern generator network

Abstract: Bath application of dopamine modifies the rhythmic motor pattern generated by the 14 neuron pyloric network in the stomatogastric ganglion of the spiny lobster, Panulirus interruptus. Among other effects, dopamine excites many of the pyloric constrictor (PY) neurons to fire at high frequency and phase-advances the timing of their activity in the motor pattern. These responses arise in part from direct actions of dopamine to modulate the intrinsic electrophysiological properties of the PY cells, and can be stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
111
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(112 citation statements)
references
References 49 publications
1
111
0
Order By: Relevance
“…In the presence of DA, it appears that the synaptic input to the AB-PD pacemaker kernel from the LP and VD neurons plays no significant role in determining the final DA-induced cycle frequency. This is despite the fact that DA strongly excites the LP neuron (Flamm and HarrisWarrick, 1986b;Harris-Warrick et al, 1995a) and enhances LP inhibition of the PD neurons (Johnson et al, 1995). The quantitative effect of DA on LP activity provides an explanation for this result.…”
Section: Effects Of Dopamine Serotonin and Octopamine On The Pylorimentioning
confidence: 99%
“…In the presence of DA, it appears that the synaptic input to the AB-PD pacemaker kernel from the LP and VD neurons plays no significant role in determining the final DA-induced cycle frequency. This is despite the fact that DA strongly excites the LP neuron (Flamm and HarrisWarrick, 1986b;Harris-Warrick et al, 1995a) and enhances LP inhibition of the PD neurons (Johnson et al, 1995). The quantitative effect of DA on LP activity provides an explanation for this result.…”
Section: Effects Of Dopamine Serotonin and Octopamine On The Pylorimentioning
confidence: 99%
“…Furthermore, application of the neuromodulator dopamine to the intact network leads to an increase in cycle frequency through variable mechanisms in different cell types (Harris-Warrick et al, 1998). In the pyloric constrictor (PY) cells, for example, dopamine decreases the delay to onset of firing and increases firing frequency, effects mediated by a reduction in I A (Harris-Warrick et al, 1995a). Taken together, these studies have beautifully demonstrated the dynamic interaction of intrinsic properties and network activity, and the harmonisation of the control of these properties and the network by neuromodulators.…”
Section: Neuronal Intrinsic Properties and Rhythm Generationmentioning
confidence: 99%
“…A wealth of information exists on the monoaminergic modulation of ion currents and neuronal firing properties (Flamm and Harris-Warrick, 1986;HarrisWarrick et al, 1995b;Harris-Warrick et al, 1995a;Harris-Warrick et al, 1998;Kloppenburg et al, 1999;Johnson et al, 2003), but nothing is known about the transduction cascades mediating these effects. To extend the usefulness of this model system and gain insight into how component neurons integrate biochemical and electrical processes, we have begun a molecular characterization of DARs in this central pattern generator (CPG).…”
Section: Introductionmentioning
confidence: 99%